The Impact of Herzberg's Two Factor Theory and Efficiency at Work - Bexheti, Luljeta; Bexheti, Agron (European Journal of Multidisciplinary Studies, 2016)
This study aims to find out whether there is connectivity relation between motivation and productivity at work in the retail industry. The basic theory of this research is the Herzberg’s two factor theory, concretely motivational and hygienic factors. Another goal is to see which of the two factors of Herzberg theory have more impact in raising the productivity of the employees in the retail industry. The study sample included employees at the company JYSK, Skopje City Mall in Macedonia. The main techniques used for collecting the data for the study is the primarily designed questionnaire used to measure these indicators. Regarding the first objective of the study, the results show a high correlation between motivational-hygiene factors and increasing productivity. The results of the second goal of this study show that hygienic factors dominate more on raising of the productivity than motivational factors, which means that for employees the most important is the monthly salary, relationships with others, being secured etc. One of the key recommendations is that the executive management of the organization to maintain the right attitude in relation to hygiene factors, because for the employees at any organization it is very important the management also to approve and implement other methods for promoting motivational factors.
Keywords: productivity, hygienic factors, motivational factors, retail